Desenvolvimento rural sustentável e agricultura familiar: diagnóstico participativo de indicadores econômicos, sociais e ambientais na região Oeste do Paraná - Ribeiro, Rita de Cássia (2015)
This research addresses the issue of sustainable rural development from the perspective of farmers, including the economic, social and environmental demands presented by these social actors of Paraná west. The research was conducted in order to ascertain the perception of farmers about the challenges and barriers to sustainable rural development, the cutout defined by the "Public-Lot Call 36" -West Paraná, resulting from contract between Emater Institute and Ministry of Agrarian Development, with coverage of nine municipalities (Formosa, Guaíra, Jesuítas, Marechal Cândido Rondon, Nova Santa Rosa, Santa Helena, Toledo, Tupãssi, Ubiratã). It started from the assumption that the family farmers, that beyond the economic dimension, possess broad awareness of other dimensions of sustainability, with emphasis on environmental and social issues. The field work of the technicians of the Institute Emater occurred by conducting 97 meetings, using the methodological tool of Participatory Rural Appraisal. The indicators obtained in rural areas were grouped into dimensions for analysis and discussion. Data were subjected to SPSS (Statistical Package for the Social Sciences), version 20.0 for Windows. The results showed that the concerns of family farmers in the west of Paraná, are not restricted only to economic, but denote concern for future generations, with demands for social and environmental reasons